MicroRNA-mediated metabolic regulation of immune cells in cancer: an updated review - Khameneh, Sepideh Chowdary; Razi, Sara; Lashanizadegan, Ramin; Akbari, Sanaz; Sayaf, Masoud; Haghani, Karimeh; Bakhtiyari, Salar (Frontiers in Immunology, 2024)
The study of immunometabolism, which examines how immune cells regulate their metabolism to maintain optimal performance, has become an important area of focus in cancer immunology.Recent advancements in this field have highlighted the intricate connection between metabolism and immune cell function, emphasizing the need for further research. MicroRNAs (miRNAs) have gained attention for their ability to post-transcriptionally regulate gene expression and impact various biological processes, including immune function and cancer progression. While the role of miRNAs in immunometabolism is still being explored, recent studies have demonstrated their significant influence on the metabolic activity of immune cells, such as macrophages, T cells, B cells, and dendritic cells, particularly in cancer contexts. Disrupted immune cell metabolism is a hallmark of cancer progression, and miRNAs have been linked to this process. Understanding the precise impact of miRNAs on immune cell metabolism in cancer is essential for the development of immunotherapeutic approaches. Targeting miRNAs may hold potential for creating groundbreaking cancer immunotherapies to reshape the tumor environment and improve treatment outcomes. In summary, the recognition of miRNAs as key regulators of immune cell metabolism across various cancers offers promising potential for refining cancer immunotherapies. Further investigation into how miRNAs affect immune cell metabolism could identify novel therapeutic targets and lead to the development of innovative cancer immunotherapies.